Snorkel-biochar coupling enhances organic matter and nitrogen pollutant removal while mitigating greenhouse gas emissions through spatial redox regulation in bioretention systems - Ruohan Li; Wenying Sun; Yuepeng Deng; Hengxin Liu; Mingyue Yang; Yueming Han; Lixun Zhang (Water Research, 2026)

Global inequalities in non-carcinogenic health risks associated with drinking arsenic-contaminated groundwater - Ruohan Wu; Qinchuan Xin; Yin Yang; Ying Sun; Xuewen Zhou; Yongjian Ruan; Kun Xiao; Taiyuan Chen; Jianxiu Qiu (Journal of Hazardous Materials, 2026)

Targeting programmed cell death: a novel therapeutic paradigm for cancer based on mode-of-death classification - Xi Qiao; Ting Ye; Tinggai Wu; Xu Han; Tiantian Sun; Haiqiang Wang; Junru Jia; Yuanyuan Dai; Ruohan Yun; Shuo Jiang; Yuming Qin; Zhenzhen Liu; et al. (Apoptosis, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Rap1b is a critical regulator of germinal vesicle breakdown in porcine oocytes - Mingyue Sui; Zhihao Wang; Jianqiang Sun; Ruohan Mei; Mingju Sun; Yichen Liu; Xiang Gao; Youwei Li; Yanjun Huan (Theriogenology, 2026)

Wind-driven variability in phytoplankton dynamics in a semi-enclosed sea - Ruohan Sun; Xinyi Kang; Zhen Wang; Haibo Zhang; Hang Yin (Estuarine, Coastal and Shelf Science, 2026)

A novel TpAQ-COF/ZnS/ZnIn2S4 ternary photocatalyst with double Z-scheme heterostructure for visible light photocatalytic degradation of 2,4-dichlorophenol - Ruohan Sun; Yuqing Xia; Tingting Ma; Hui Yu; Guixia Liu; Jinxian Wang; Wensheng Yu; Feng Sun; Xiangting Dong (Journal of Cleaner Production, 2026)

A sensitive method for rapid determination of 256 semi-volatile organic compounds (SVOCs) in water by solid-phase extraction and GC–MS/MS - Youchang Zhu; Ruohan Sun; Yanran Dong; Yan Liu; Yupeng Chen; Zhiquan Yuan; Baozhu Pan; Nan Xu (Journal of Environmental Sciences, 2026)

Freeze–thaw impacts on the mechanical behavior of silty clay: Insights from experimental and DEM investigation - Run Liu; Rui Zhang; Ruohan Sun (Bulletin of Engineering Geology and the Environment, 2025)

Long-term exposure to dust in fine particulate matter and post-stroke functional impairment—Findings from the China National Stroke Screening Surveys - Zhaoyang Pan; Xueyan Han; Man Cao; Ruohan Wang; Jian Guo; Wei Sun; Jiarun Mi; Yuanli Liu; Tao Xue; Tianjia Guan (Journal of Hazardous Materials, 2025)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

A DEM-based approach for modeling the thermal-mechanical behavior of frozen soil - Ruohan Sun; Run Liu; Huan Zhang; Rui Zhang; Yu Jiang; Ruilong Yin (European Journal of Environmental and Civil Engineering, 2024)

Anisotropic In-Plane strain engineering Ni(OH)2 to activate alkaline hydrogen evolution reaction - Wenda Zhong; Ruohan Yu; Weilong Cao; Le Sun; Yi Yang; Ingo Manke; Chao Yang; Kangning Zhao (Chemical Engineering Journal, 2023)

DEM investigation of the mechanical behavior of frozen soil along various stress paths - Ruohan Sun; Run Liu; Huan Zhang; Chun Liu; Chengfeng Li (Bulletin of Engineering Geology and the Environment, 2023)

Polybrominated diphenyl ethers in water, suspended particulate matter, and sediment of reservoirs and their tributaries in Shenzhen, a mega city in South China - Tingting Zhu; Youchang Zhu; Yunlang Liu; Chen Deng; Xiujuan Qi; Jinling Wang; Zhizhi Shen; Donggao Yin; Yihong Liu; Ruohan Sun; Weiling Sun; Nan Xu (Environmental Science and Pollution Research, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Developing a highly efficient regeneration system for leaves of tissue-cultured tetraploid Robinia pseudoacacia L. - Xiuyu Li; Qi Guo; Chao Han; Juan Li; Li Dong; Sen Cao; Zijie Zhang; Yuhan Sun; Ruohan Wang; Yun Li (In Vitro Cellular & Developmental Biology - Plant, 2022)

Constant hypoxia inhibits osteoclast differentiation and bone resorption by regulating phosphorylation of JNK and IκBα - Zhenzhen Ma; Ruohan Yu; Jinxia Zhao; Lin Sun; Leilei Jian; Changhong Li; Xiangyuan Liu (Inflammation Research, 2019)